Low Back Pain in a Natural Disaster. Issue 2 (14th June 2013) - Angeletti, Chiara; Guetti, Cristiana; Ursini, Maria L.; Taylor, Robert; Papola, Roberta; Petrucci, Emiliano; Ciccozzi, Alessandra; Paladini, Antonella; Marinangeli, Franco; Pergolizzi, Joseph; Varrassi, Giustino
Abstract Low back pain is usually self‐limited. The transition from acute to chronic LBP is influenced by physical and psychological factors. Identification of all contributing factors, in a mass emergency setting, differentiating primary and secondary life‐threatening forms of LBP, is the best approach for success. Aims of the present report were to estimate the prevalence of LBP in population afferent to four advanced medical presidiums (AMPs) during postseismic emergency period and to evaluate frequency of use, types of pain killers administered to patients and short‐term efficacy of them. Methods Study was carried out in four AMPs during the first 5 weeks after the earthquake. Site, type of eventual trauma, pain intensity during LBP episode by Verbal Numerical Rating Scale (vNRS) were registered. Diagnosis of primary or secondary LBP was made on the basis of clinical features and therapeutic treatment was also analyzed. Results The prevalence of acute LBP was 4.9% (95%, IC 3.7 to 6.4), among 958 first accesses to AMP, representing 14.1% (95%, IC 10.8 to 18.3) of cases on the total of 322 patients treated for all pain conditions. Episodes of relapsed LBP in chronic pre‐existing LBP represented the 40% (n = 19) of cases, while the first episode was present in 60% of patients (n = 28). Pain treatment was effective with a significant reduction in vNRS in short term evaluation. Conclusions The emotional stress induced by natural disaster tends to heighten norepinephrine and sympathetic nervous system activity, which may further amplify nociception through peripheral or central mechanisms that result in consistent prevalence of primary NSLBP and become potential risk factor for pain chronicization.